PENGARUH KONSENTRASI TAPIOKA PADA BERAS VARIETAS MENTIK (Oryza sativa var. Mentik) TERHADAP SIFAT FISIKOKIMIA RICE PAPER - Putriningsih, Agnes Ayu; Surjoseputro, Sutarjo; Setijawati, Erni (Widya Mandala Surabaya Catholic University, 2018)
Rice paper wrappers are made from rice that can be directly consumed and comes from Asia. Rice paper has the characteristic appearance of the translucent, elastic, easily foldable and not easily torn. Rice paper begins manufacture of soaking rice overnight and then in doing demolition by adding water until the rice porridge, after it is done printing on the steamer until drying. In preliminary studies using Mentik rice only produce rice paper that is easily torn and less elastic after being printed or when used. The addition of tapioca expected to improve the initial structure of rice paper with the ability to provide a stable due role in maintaining water amylopectin gel systems. This study uses a randomized block design (RAK) factorial design with one factor, namely the concentration of tapioca. The concentration of starch to be used is 0% (P1); 0.25% (P2); 0.5% (P3); 0.75% (P4); 1% (P5); 1.25% (P6) and 1.5% (P7) of the weight of the rice dough is used. Repetition of the experiments were carried out four times to obtain a total of 28 experimental units. Data were analyzed using ANOVA (Analysis of Varians) test at α = 5%, if the results showed a significant effect, the next analyzed by followed by DMRT (Duncan’s Multiple Range Test) at α = 5% to determine the combination treatment that gave a significant difference. Analysis performed is the water content, aw, and power rehydration. The results showed that the effect of tapioca give effect to the physicochemical characteristics of rice paper. The water content increased while the rice paper rice paper rehydration power decrease with increasing concentration of tapioca. Water content ranging from 12.11% - 15.54%, power rehydration ranging from 110.42% - 113.04% and aw values ranged from 0.54 to 0.68. Tapioca concentration of 1.25% is the best treatment to the value of the water content of 14.85%, 118.59% and the power rehydration aw 0.67.